LEARNING MANAGEMENT IN THE FRAMEWORK OF IMPROVING LEARNING ACHIEVEMENT IN STUDENTS - Darwin Nasution; Afridah Afridah (Sean Institute, 2023)
Educational management is an important component in education that can affect the quality of the teaching and learning process and the learning outcomes. Therefore this study aims to examine the role of education management in improving student achievement. The research method used is qualitative research, with data collection techniques through observation, interviews, and documentation. The data analysis used is the Miles and Hubermar model which consists of data reduction, data validity and conclusion/verification. The results of this study indicate that learning activities based on planned learning concepts and principles have a high level of urgency in achieving learning objectives. This is because planning that is full of consideration and maturity can create conditions or atmosphere for learning that is more effective, efficient and productive, as well as with appropriate learning strategies, because lecturers as professionals have a variety of special skills and abilities that can be pursued to improve the quality of student learning